ECONOMIC PROJECTION OF BALIKPAPAN AS A BUFFERING CITY FOR INDONESIA’S NEW CAPITAL - Silfiani, Mega; Fitriani, Yustina (Statistics Study Programme, Department of Mathematics, Faculty of Mathematics and Natural Sciences, University of Pattimura, 2025)
As part of Indonesia’s capital relocation plan to East Kalimantan, Balikpapan plays a critical role as a supporting city, facing opportunities and challenges in infrastructure, economic stability, and public services. This study forecasts two key economic indicators: monthly inflation and annual Gross Regional Domestic Product (GRDP), using Error, Trend, Seasonal (ETS) and Autoregressive Integrated Moving Average (ARIMA) methods. For monthly inflation, the SARIMA(0,1,1)(1,0,0)12 model outperforms ETS(A,N,N) with a lower RMSE, providing higher accuracy in capturing inflation dynamics. For annual GRDP, both ETS(A,N,N) and ARIMA(0,0,0) yield similar accuracy, with ARIMA slightly better. These findings support data-driven planning to maintain price stability and foster economic growth. Accurate projections ensure Balikpapan’s readiness as a sustainable, resilient city, aligning with SDG 8 (Economic Growth) and SDG 11 (Sustainable Cities and Communities).